VD_FINDINFO Arrêt / 2013 / 741 vom 8. Oktober 2013 - VD Tribunal cantonal (2013)
RETRAIT DE L'AUTORITÉ PARENTALE, REJET DE LA DEMANDE, AUTORITÉ PARENTALE CONJOINTE | 14 al. 1 Tit. fin. CC, 14a Tit. fin. CC, 298a al. 2 CC, 450 CC